Ross River virus in a joint military exercise - Hueston, Linda; Yund, Alun; Cope, Stanton; Monteville, Marshall; Marchetti, Marie; Haniotis, John; Clancy, John; Doggett, Stephen; Russell, Richard; Dwyer, Dominic; et al. (Communicable Diseases Intelligence, 1997)
In support of a large, combined Australia-United States of America military exercise at Shoalwater Bay in south-eastern Queensland during March 1997 (TANDEM THRUST 97), the United States Navy sent the Deployed Public Health Laboratory (DPHL) into the field with the forces. The purpose of this was preventative medicine as well as disease and vector surveillance. Among the numerous potential threats to the health of the troops was Ross River virus (RRV), to which very few of the US personnel would have been previously exposed.